تجلِّيات المكان ودلالاته في المُنجز الرِّوائي اللّيبي رواية "أم الزين" لـ(غالية الذرعاني) أنموذجاً (Comprehensive Journal of Science, 2025)
Manifestations of Place and Its Connotations in the Liban Novel Achievement (Umm Al-Zain) Novel by (Ghalia Al-Dharaani) as a ModelHala Saad Ali AhmedAssistant Lecturer, Department of Arabic Language, Faculty of Arts, Ajilat – University of ZawiaAbstract:                              The element of (place) is a fertile field for enriching narrative texts in the field of literary criticism, We find it replete with a huge amount of scholars' opinions and efforts, Some consider it a geographical and geometric place with borders that frame the literary text, while others consider it merely a physical space used by the self to achieve its goals, There are those who believe that pace cannot remain static, because it is living element that generates symbolic and social connotations through the writer's imaginative addition of his literary text, Thus, place contributes to the development of the character that produces events, In studying the novel (Umm al-Zein), we find that it does not contain many places, This is due to the structure of the novel and what it requires, Although the places were few, they carried profound connotations sufficient to convey the meanings of the text.
Keywords: manifestation, novelistic achievement, familiarity, Umm al-Zein, place and its connotations